HPV-associated cervical diseases: screening, methods of examination, principles of treatment - Vera N Prilepskaya (IP Berlin A.V., 2019)
This article presents information about modern principles of diagnosis and treatment of HPV-associated diseases. Behind cervical cancer morbidity and mortality rates over the past 10 years increase significantly. Examination and observation of patients with human papillomavirus persistence of highly oncogenic types is important a link in cancer prevention. The article presents diagnostic methods, treatment of cervical diseases, as well as the possibility of pharmacotherapy in HPV-associated diseases.